An Isoquinolin‐1(2H)‐Imine Derivative Induces Cell Death via Generation of Reactive Oxygen Species and Activation of JNK in Human A549 Cancer Cells. Issue 12 (31st May 2017) - Liu, Jing; Liu, Tongyang; Mou, Hanchuan; Jia, Shuting; Huang, Chao; Yan, Shengjiao; Lin, Jun; Luo, Ying; Zhang, Jihong
ABSTRACT: Compound 11‐benzoyl‐10‐chloro‐7, 9‐difluoro‐6‐imino‐2, 3, 4, 6‐tetrahydro‐1H‐pyrimido[1, 2‐b]isoquinoline‐8‐carbonitrile (HC6h) is a novel polyhalo 1, 3‐diazaheterocycle fused isoquinolin‐1(2H)‐imines derivative, which displays good anticancer activity and low toxicity in vivo. However, the underlying anticancer mechanisms have not previously been identified. The proliferation of A549 was assessed by MTT assay. The reactive oxygen species (ROS) level was assessed in A549 with a H2 DCFDA probe. Mitochondrial membrane potential was measured using the JC‐1 staining. Apoptosis were measured by annexin‐V/PI assay and autophagy by acridine orange staining and GFP‐LC3 fluorescence assay. The expression of autophagic and apoptotic proteins was determined by Western blot. The compound HC6h increased accumulation of vesicles, acridine orange‐stained cells and LC3‐II in A549 cells. Inhibition of compound HC6h‐induced autophagy by bafilomycin A1 increased apoptosis. Compound HC6h enhanced activation of caspase‐3, caspase‐9 and PARP cleavage in A549 cells. Compound HC6h leads to the rapid generation of intracellular ROS. Moreover, compound HC6h induced phosphorylation of JNK and was conferred by the increased ROS levels. Furthermore, down‐regulation of JNK attenuated autophagic and apoptotic effect in response to HC6h. The induction of ROS upon HC6h treatment leads to the activation of JNK that mediates autophagy and apoptosis in human A549 cancer cells. J. Cell. Biochem. 118: 4394–4403, 2017. © 2017 Wiley Periodicals, Inc. Abstract : HC6h induced apoptosis and autophagy via the ROS‐dependent JNK signaling pathway in A549 cells. Cancer cells activated incomplete autophagy with HC6h treatment and inhibition of autophagy by autophagy inhibitor significantly augmented cell death on HC6h treatment.